Differences in isometric strength and sprinting speed of academy soccer players: a special interest in transition between the age groups and national team selected players - Mikulič, Martin; Cholp, Jozef; Nagy, Nikolas; Skala, Filip (Frontiers in Sports and Active Living, 2025)
Players in European soccer academies frequently advance from the lower to the higher age group. Underdevelopment of their strength and speed capacities increases the risk of injury. On the one hand, this study compared the isometric strength and speed performance of elite youth soccer players regarding age groups. Further, it aimed to recognize differences in relative isometric strength between the national team selected and non-selected academy players. Eighty-three academy players from five age groups of single academy were compared in isometric peak force production in a bilateral knee flexion test (ISO 30°), abduction and adduction tests (ABD and ADD 60°). Their sprinting speed was evaluated by 10 and 30 meter sprint tests, and the 505 change of direction test (COD 180°). Significant age group effects were discovered for absolute isometric strength (p = < 0.001; η2 = 0.40–0.43) but relative strength differed only between U15 and U19 in ISO 30° (p = 0.04; ES = 1.04). The U14 players were slower than all groups (ES = 0.95–3.68) excluding the U15. These players were slower than U16, U17, and U19 (ES = 1.07–2.37), while U17 overpassed U19 in 180° COD (p = 0.02; ES = 0.22). Consequently, sprinting speed demands are of special interest in the transition of players from the U15 to the U16 age group. The national team players were not relatively stronger in ISO 30° (–0.08 N/kg, p = 0.70; ES = 0.10), ABD 60° (–0.14 N/kg, p = 0.59; ES = 0.13), and ADD 60° (–0.33 N/kg, p = 0.22; ES = 0.31) compared to their academy peers This suggests that maximal relative isometric strength is not of special interest for the selection of academy soccer players to the national team squad.